A blocked benzoxazine resin, a bisphthalonitrile-based composite material containing the same, and a composite cured resin

By introducing spirocyclic acetal structure into benzoxazine resin, the problem of difficulty in degradation and recycling after curing is solved, the acidic or high-temperature degradation and recycling of the material is achieved, and environmental benefits are improved.

CN115490824BActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110672506.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-17
Publication Date
2025-02-28
Estimated Expiration
2041-06-17

AI Technical Summary

Technical Problem

The existing benzoxazine resins are difficult to degrade and recover after curing, which limits their application and recycling in the field of thermosetting resins.

Method used

A low-molecular-weight main chain benzoxazine resin containing a spirocyclic acetal structure is used, and degraded through acidic or high-temperature conditions to achieve recycling of the material.

Benefits of technology

By introducing acetal structure, the material is given acid sensitivity, degradation and recycling under acidic or high temperature conditions are achieved, and the environmental benefits and recycling capabilities of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115490824B_ABST
    Figure CN115490824B_ABST
Patent Text Reader

Abstract

The present invention discloses a blocked benzoxazine resin, a diphthalonitrile-based composite material and a composite cured resin containing the blocked benzoxazine resin. The blocked benzoxazine resin is a main chain polymer, and the molecular chain end of the main chain polymer is a structure shown in one of formulas (I-4) to (I-9): in formulas (I-1) to (I-9), each R is independently selected from one of aliphatic groups and derivatives thereof, alicyclic groups and derivatives thereof, and aromatic groups and derivatives thereof; and / or, in formulas (I-4) to (I-6), R' is selected from one of aliphatic groups and derivatives thereof, alicyclic groups and derivatives thereof, and aromatic groups and derivatives thereof; and / or, in formulas (I-7) to (I-9), R1" to R4" are independently selected from one of hydrogen, aliphatic groups and derivatives thereof, alicyclic groups and derivatives thereof, and aromatic groups and derivatives thereof. The acetal introduced into the end-capped benzoxazine resin of the present invention is a spirocyclic acetal, which has a certain rigidity, and can endow the benzoxazine resin with good heat resistance during the curing process, and endow the cured resin with heat resistance and rigidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of benzoxazine, and in particular to a blocked benzoxazine resin, a diphthalonitrile-based composite material containing the same, and a composite cured resin. Background Art

[0002] With the development of emerging industries such as large aircraft, new energy, and rail transportation in my country, the application fields of thermosetting resin-based composite materials are constantly expanding, and their recycling issues are becoming more and more prominent. Many research institutions at home and abroad have proposed relevant topics to study their recycling issues [Chemical Information. Ningbo Institute of Materials has made progress in the research on green recycling of composite materials [J]. New Chemical Materials, 2013 (2): 168-168.].

[0003] Many experts and scholars at home and abroad have conducted relevant research on the degradation and recycling of thermosetting resins. The main methods include physical and chemical methods. The physical method mainly uses mechanical crushing and recycling, and the chemical method mainly includes pyrolysis and solvent methods [Xu Pinglai, Li Juan, Li Xiaoqian. Research progress on recycling methods of thermosetting resin-based composite materials [J]. Engineering Plastics Application, 2013, 41 (1): 100-104.]. Hou Xianglin's team at Shanxi Coal Chemistry Research Institute used unsaturated zinc ions to selectively break the carbon-nitrogen bonds of epoxy resins, achieving efficient degradation and recycling of carbon fiber reinforced epoxy resins; and used weakly coordinated aluminum ions to selectively break ester bonds to achieve degradation and recycling of glass fiber reinforced unsaturated polyester resins [Deng TS, Liu Y, Cui XJ, et al. Cleavage of CN bonds in carbon fiber / epoxy resin composites. Green Chemistry, 2015, 17, 2141-2145.]. T.Iwaya et al. degraded unsaturated polyester in a solvent of diethylene glycol monomethyl ether and phenylethanol, reacted at 190-350°C for 1-8 hours under the catalysis of K3PO4, and recovered long glass fibers [Iwaya T, et al. Recycling of fiber reinforced plastics using depolymerization by solvothermal reaction with catalyst. J Mater Sci, 2008, 43(7): 2452–2456.].

[0004] In my country, the treatment of thermosetting composite waste mainly adopts landfill and incineration. The landfill method occupies land resources and causes soil damage. Incineration does not cause land waste, but it will cause secondary pollution due to the large amount of toxic gas produced during combustion, and there are potential and unknown dangers [Chemical Information. Ningbo Institute of Materials has made progress in the research of green recycling of composite materials [J]. New Chemical Materials, 2013 (2): 168-168.].

[0005] Therefore, developing a decomposable thermosetting resin system is an effective way to recycle waste thermosetting resins and their adhesives, coating materials, and composite materials, and is also one of the important development directions in the field of thermosetting resins. Summary of the invention

[0006] Benzoxazine resin (BZ) is a new type of thermosetting resin. It is a nitrogen- and oxygen-containing six-membered heterocyclic compound obtained by condensation reaction of phenolic, aldehyde and amine compounds. The material obtained after curing, benzoxazine resin, has good heat resistance and flame retardancy of traditional phenolic resin. Since no volatile small molecules are released during the ring-opening curing process, the thermal curing shrinkage rate is close to zero. The cured polybenzoxazine resin has a low porosity, and almost no internal stress and cracks, which is conducive to the processing and molding of the finished product and maintaining the size of the product. At the same time, there is almost no free aldehyde and phenol in benzoxazine resin, which can be used as a flame retardant material for cabins and is widely used in various fields such as construction, transportation, aviation, aerospace, electronics, ships, and energy [Guo Jun. Domestic and foreign composite waste recycling technology and development status [J]. Science and Technology Innovation Herald, 2011 (33): 99-100.].

[0007] At the same time, benzoxazines still have some disadvantages, such as high curing temperature, generally reaching 200°C; long curing time; the benzoxazines obtained after the traditional benzoxazines polymerization are brittle and the mechanical properties are not very high; the processing process is complicated, most of the benzoxazines monomers are solid, and they are difficult to use as conveniently as liquid thermosetting resin prepolymers during processing; the prepolymers have low molecular weight and are difficult to process into films. On the other hand, the high molecular weight linear structure is a double-edged sword. As the material properties improve, the preparation and processing become difficult. The prepolymers tend to form gels during the synthesis stage, which makes the reaction time control and solvent selection important and complicated. On the other hand, even at very high temperatures, most MCBPs still have high viscosity and characteristics that are not suitable for conventional melt processing. To date, polybenzoxazines derived from MCBP mostly appear in the form of films due to solution casting.

[0008] The cross-linked network structure of benzoxazine resin after curing is insoluble and infusible, which greatly limits their application in terms of recycling and degradability. How to degrade and recycle the cured benzoxazine is a very realistic problem. Under the guidance of national policies, we should vigorously develop industrial recycling and reuse processes of thermosetting carbon fiber composite waste with low energy consumption and good recycling effect, and realize the resource recycling and reuse of composite waste. This is of great significance to building a resource-saving, environmentally friendly and harmonious society, and responding to the call for environmental protection, energy conservation and emission reduction, and sustainable development at home and abroad [Liu Jianye, Song Jinmei, Peng Yugang, et al. Current status of recycling and reuse of thermosetting carbon fiber composite waste [J]. New Chemical Materials, 2014 (8): 216-218.].

[0009] In order to overcome the above problems, the present invention discloses a blocked benzoxazine resin, a diphthalonitrile-based composite material and a composite cured resin containing the same. The blocked benzoxazine resin having a main chain structure is a low molecular weight main chain containing a spiroacetal structure. The benzoxazine resin and the composite material or cured product containing the same can be degraded in acidic or high temperature conditions. After separation and recovery of the degradation products, the recycling of the materials can be achieved, thereby completing the present invention.

[0010] One of the objects of the present invention is to provide a terminal benzoxazine resin, which is a main chain polymer, wherein the main chain polymer contains at least one of the repeating units represented by formula (I-1) to formula (I-3) in the molecular chain:

[0011]

[0012] The molecular chain end of the main chain polymer is a structure shown in one of formulas (I-4) to (I-9):

[0013]

[0014]

[0015] In formulas (I-1) to (I-9), each R is independently selected from one of aliphatic groups and their derivatives, alicyclic groups and their derivatives, and aromatic groups and their derivatives; and / or, in formulas (I-4) to (I-6), R′ is selected from one of aliphatic groups and their derivatives, alicyclic groups and their derivatives, and aromatic groups and their derivatives; and / or, in formulas (I-7) to (I-9), R1″ to R4″ are independently selected from one of hydrogen, aliphatic groups and their derivatives, alicyclic groups and their derivatives, and aromatic groups and their derivatives.

[0016] Among them, the acetal structure contained in the blocked benzoxazine resin can give the material acid sensitivity, achieve degradation under acidic conditions, be beneficial to the recycling of materials, and have good environmental benefits. Further, the acetal structure used in the present invention is a spiroacetal, which is a closed six-membered ring structure with certain rigidity, giving the benzoxazine resin good heat resistance during the curing process, and giving the cured resin heat resistance and rigidity.

[0017] In a preferred embodiment, in formula (I-1) to (I-9), each R is independently selected from at least one of a C2-C20 alkyl group and its derivatives, a C6-C20 aryl group and its derivatives, a C6-C20 alicyclic group and its derivatives; and / or, in formula (I-4) to (I-6), R′ is selected from a C1-C12 alkyl group, a C6-C12 alicyclic group, a phenyl group or a substituted phenyl group; and / or, in formula (I-7) to (I-9), R1″ to R4″ are independently selected from hydrogen, a C1-C12 alkyl group, a C6-C12 alicyclic group or a phenyl group.

[0018] In a further preferred embodiment, in formula (I-1) to (I-9), each R is independently selected from at least one of a C2-C10 alkyl group and its derivatives, a C6-C10 aryl group and its derivatives, a C6-C10 alicyclic group and its derivatives; and / or, in formula (I-4) to (I-6), R′ is selected from a C1-C6 alkyl group, a C6-C8 alicyclic group or a phenyl group; and / or, in formula (I-7) to (I-9), R1″ to R4″ are independently selected from hydrogen, a C1-C6 alkyl group, a C6-C8 alicyclic group or a phenyl group.

[0019] For example, in formula (I-1) to formula (I-9), R is selected from: C2 to C10 alkyl, phenyl,

[0020]

[0021] In a further preferred embodiment, the end-capped benzoxazine resin is selected from at least one of the polymers of formula (i-1) to formula (i-6):

[0022]

[0023]

[0024] In formula (i-1) to formula (i-6), n is 2 to 20, preferably 4 to 14, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20. In formula (i-1) to formula (i-6), R, R', R1" to R4" have the same definitions as above.

[0025] The second object of the present invention is to provide a method for preparing the blocked benzoxazine resin described in the first object of the present invention, comprising: mixing a monoamine compound and / or a monophenol compound with a bisphenol compound containing a spiroacetal structure, a diamine compound, and an aldehyde compound for reaction, and obtaining the blocked benzoxazine resin through post-treatment.

[0026] The method can be carried out by using a solution method, a solvent-free method and a suspension method disclosed in the prior art, and the solution method is preferred.

[0027] In a preferred embodiment, the bisphenol compound containing a spiroacetal structure is selected from at least one of pentaerythritol di-p-hydroxybenzaldehyde (p-SQ) as shown in formula (II), pentaerythritol di-m-hydroxybenzaldehyde (m-SQ) as shown in formula (III), pentaerythritol di-o-hydroxybenzaldehyde (o-SQ) as shown in formula (IV), and their derivatives:

[0028]

[0029] In a preferred embodiment, the diamine compound is at least one selected from aliphatic diamines and derivatives thereof, aromatic diamines and derivatives thereof, and alicyclic diamines and derivatives thereof.

[0030] In a further preferred embodiment, the diamine compound is selected from at least one of C2-C20 aliphatic diamines and derivatives thereof, C6-C20 aromatic diamines and derivatives thereof, and C6-C20 alicyclic diamines and derivatives thereof.

[0031] In a further preferred embodiment, the diamine compound is at least one selected from C2-C10 aliphatic diamines and derivatives thereof, C6-C10 aromatic diamines and derivatives thereof, and C6-C10 alicyclic diamines and derivatives thereof.

[0032] For example, the diamine compound is selected from at least one of ethylenediamine, butanediamine, hexamethylenediamine, octanediamine, decanediamine, 1,12-diaminododecane, p-phenylenediamine, 4,4'-diaminodiphenylmethane, diaminodiphenyl sulfone, and 4,4'-methylenebis(2-methylcyclohexylamine).

[0033] In a preferred embodiment, the aldehyde compound is selected from paraformaldehyde and / or formaldehyde aqueous solution, preferably paraformaldehyde.

[0034] Wherein, when formaldehyde aqueous solution is selected, its concentration is 37%.

[0035] In a preferred embodiment, the ratio of the bisphenol compound containing a spiroacetal structure, the diamine compound and the aldehyde compound is 1:1:(2-5).

[0036] In a further preferred embodiment, the molar ratio of the bisphenol compound containing a spiroacetal structure, the diamine compound and the aldehyde compound is 1:1:(2-3).

[0037] The molar amount of the bisphenol compound containing the spiroacetal structure is calculated based on the molar amount of the phenolic hydroxyl groups therein, the molar amount of the diamine compound is calculated based on the molar amount of the amine groups therein, and the molar amount of the aldehyde compound is calculated based on the molar amount of the aldehyde groups therein.

[0038] In a preferred embodiment, the structure of the monoamine compound is R′-NH2.

[0039] In a further preferred embodiment, the monoamine compound is at least one selected from aniline, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, neopentylamine, dodecylamine and octadecylamine.

[0040] In a preferred embodiment, the monophenol compound is selected from at least one of phenol and substituted phenol.

[0041] In a preferred embodiment, the molar ratio of the total mole of the monoamine compound and the monophenol compound to the molar ratio of the bisphenol compound containing the spiroacetal structure is (1-2):1, preferably (1-1.2):1, for example 1:1; and / or,

[0042] In a further preferred embodiment, the molar ratio of the monoamine compound to the monophenol compound is (0-10):(10-0).

[0043] In a preferred embodiment, when the monoamine compound and / or the monophenol compound are mixed with the aldehyde compound, the bisphenol compound containing a spiroacetal structure, and the diamine compound for reaction, the reaction temperature is 80 to 150° C., preferably 90 to 130° C.; and / or the reaction time is 0.2 to 5 hours, preferably 0.5 to 2 hours.

[0044] In a preferred embodiment, the method comprises the following steps:

[0045] Step 1, mixing the aldehyde compound, the bisphenol compound containing a spirocyclic acetal structure, the diamine compound and a solvent, and heating them for a preliminary reaction;

[0046] Step 2: After the reaction is completed, add a monoamine compound and / or a monophenol compound for end-capping;

[0047] Step 3: After the end-capping is completed, post-treatment is performed to obtain the end-capped benzoxazine resin.

[0048] In a preferred embodiment, in step 1, the solvent is selected from one or more (e.g., one or two) of ethanol, methanol, isopropanol, butanol, isobutanol, tetrahydrofuran, dioxane, toluene, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.

[0049] In a further preferred embodiment, in step 1, the solvent is selected from one or more (eg, one or two) of isopropanol, tetrahydrofuran, dioxane, toluene, dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0050] In a further preferred embodiment, in step 1, the solvent is selected from one or more (eg, one or two) of isopropanol, dioxane, and dimethylformamide.

[0051] In a preferred embodiment, in step 1, the temperature of the pre-reaction is 80-150°C, preferably 90-130°C, for example 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0052] In a further preferred embodiment, in step 1, the pre-reaction is carried out under reflux.

[0053] In a preferred embodiment, in step 1, the pre-reaction time is 0.2 to 5 hours, preferably 0.5 to 2 hours.

[0054] For example, in step 1, the reaction time is 0.2 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0055] In a preferred embodiment, in step 2, the end-capping is performed for 5 to 20 hours, preferably 10 to 12 hours.

[0056] For example, in step 2, the end-capping is performed for 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, or 20 h.

[0057] In a preferred embodiment, in step 3, the post-treatment includes alkali washing, water washing, solvent removal treatment and drying.

[0058] In a further preferred embodiment, alkali solution is used for washing until neutrality, and the weight concentration of the alkali solution is preferably 0.5-20%, preferably 1-10%.

[0059] For example, the weight concentration of the alkali solution is 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18% or 20%.

[0060] The alkali solution may be selected from at least one of alkaline aqueous solutions such as sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, sodium bicarbonate aqueous solution and potassium bicarbonate aqueous solution.

[0061] In a further preferred embodiment, the solvent is removed by filtration and then dried.

[0062] The third object of the present invention is to provide a blocked benzoxazine resin obtained by the preparation method described in the second object of the present invention.

[0063] The blocked benzoxazine resin can be subjected to ring-opening curing to obtain a cured resin.

[0064] In a preferred embodiment, the ring-opening curing is carried out at 100-240°C, preferably 120-220°C.

[0065] In a further preferred embodiment, the ring-opening curing is carried out as follows: the temperature is increased from 120° C. to 220° C., with each 20° C. being a temperature step, and each temperature step reacting for 2 hours.

[0066] Preferably, 120°C (2h) ~ 140°C (2h) ~ 160°C (2h) ~ 180°C (2h) ~ 200°C (2h) ~ 220°C (2h).

[0067] The blocked benzoxazine resin cured product of the present invention can be degraded in an acidic solution. Preferably, the benzoxazine resin cured product is immersed in an acidic solution and reacted for 8-48 hours to achieve degradation. The stronger the acidity and the longer the time, the higher the degree of chemical degradation of the cured product.

[0068] Preferably, the acid used in the acidic solution is selected from an organic acid (such as at least one of formic acid, acetic acid, trifluoromethanesulfonic acid, and trichloroacetic acid) and an inorganic acid (such as at least one of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid).

[0069] Preferably, the solvent used for the acidic solution is a common polar solvent, selected from at least one of water, alcohol compounds, ketone compounds, ether compounds, and amide compounds; more preferably, the alcohol solvent is selected from ethanol, methanol, isopropanol, butanol, isobutanol, phenylethyl alcohol, benzyl alcohol, ethylene glycol, butylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, glycerol, ethylene glycol monomethyl ether, diethylene glycol, triethylene glycol, dipropylene glycol, furfuryl alcohol, and tetrahydrofurfuryl alcohol; the ketone compound is selected from at least one of butanone and cyclohexanone; the ether compound is selected from THF and 1,4-dioxane; the amide compound is selected from at least one of DMF, DMSO, sulfolane, N-methylpyrrolidone, morpholine, and N-methylmorpholine.

[0070] A fourth object of the present invention is to provide a diphthalonitrile-based composite material, which comprises a blocked benzoxazine resin and a diphthalonitrile compound containing a spirocyclic acetal structure, wherein the blocked benzoxazine resin is selected from the blocked benzoxazine resin described in one of the objects of the present invention or the main chain benzoxazine obtained by the method described in the second object of the present invention.

[0071] Among them, the diphthalonitrile compound containing a spirocycle acetal structure contains a spirocycle acetal structure. The compound can adopt the diphthalonitrile compound containing a spirocycle acetal structure disclosed in the prior art, for example, but not limited to the reference patent CN112010833A and the document "Ke Li, Hua Yin, Kun Yang, Pei Dai, Ling Han and RiweiXu. Synthesis and properties of phthalonitrile-based resins containingspirocycle acetal. High Performance Polymers 2020", and the full text of CN112010833A and the document are introduced here.

[0072] The curing temperature of the diphthalonitrile compound containing a spiro acetal structure alone is relatively high, with the highest curing temperature being higher than 250° C., and even reaching 300-400° C. For example, in the embodiment of patent CN112010833A, the highest curing temperature reaches 375° C. However, the inventors have found through a large number of experiments that when a mixture of a diphthalonitrile compound containing a spiro acetal structure and the main-chain benzoxazine of the present invention is cured, the presence of the main-chain benzoxazine can reduce the curing temperature of the diphthalonitrile compound containing a spiro acetal structure in the mixture, and specifically, the mixture can be cured at a temperature below 250° C.

[0073] In addition, the spiroacetal structure will be destroyed at high temperatures (e.g., 250° C. and above). When curing a diphthalonitrile compound containing a spiroacetal structure alone, the maximum curing temperature is significantly higher than 250° C., which will cause the spiroacetal bond in the compound to be destroyed at high temperatures, causing the obtained cured product to lose its degradability under acidic conditions. Therefore, the cured product of a diphthalonitrile compound containing a spiroacetal structure generally cannot be degraded in acidic conditions.

[0074] In the present invention, the inventors have found through a large number of experiments that by introducing the blocked benzoxazine of the present invention into the diphthalonitrile compound containing a spiro acetal structure, the curing temperature of the diphthalonitrile compound containing a spiro acetal structure is reduced. Specifically, curing can be achieved at a temperature below 250° C. In this way, the spiro acetal bond in the diphthalonitrile compound containing a spiro acetal structure will not be destroyed, and the acidic degradability of the diphthalonitrile compound containing a spiro acetal structure is retained.

[0075] In a preferred embodiment, based on 100 wt% of the total weight of the diphthalonitrile-based composite material, the blocked benzoxazine accounts for 10 to 90 wt% and the diphthalonitrile compound containing a spiroacetal structure accounts for 10 to 90 wt%.

[0076] In a further preferred embodiment, based on 100 wt% of the total weight of the diphthalonitrile-based composite material, the blocked benzoxazine accounts for 10-50 wt% and the diphthalonitrile compound containing a spiro acetal structure accounts for 50-90 wt%.

[0077] For example, based on 100 wt% of the total weight of the diphthalonitrile-based composite material, the blocked benzoxazine accounts for 10, 20, 30, 40 or 50 wt%, and the diphthalonitrile compound containing the spirocyclic acetal structure accounts for 50, 60, 70, 80 or 90 wt%.

[0078] The fifth object of the present invention is to provide a diphthalonitrile-based composite cured resin, which is a ring-opening cured product of the diphthalonitrile-based composite material described in the fourth object of the present invention.

[0079] In a preferred embodiment, the ring-opening curing is carried out at 120-220°C; preferably, the temperature is increased from 120°C to 220°C, with each 10-30°C being a temperature gradient, and each temperature gradient is reacted for 1-3 hours.

[0080] For example, the temperature is raised from 120°C to 220°C, with each 20°C being a temperature gradient, and each temperature gradient is reacted for 2 hours to obtain a cured product.

[0081] Wherein, the diphthalonitrile-based composite curing resin can be degraded under acidic conditions.

[0082] Regarding the explanation that the resin cured with phthalonitrile compounds containing spirocycle acetal structure cannot be degraded: please refer to the literature "Ke Li, Hua Yin, Kun Yang, Pei Dai, Ling Han and Riwei Xu. Synthesis and properties of phthalonitrile-based resins containing spirocycle acetal. High Performance Polymers 2020". In this literature, experiments and analysis are clearly conducted. The resin cured with phthalonitrile compounds containing spirocycle acetal structure alone loses its degradability. The reason is that certain reactions of the spiroacetal structure may occur during the high-temperature curing process, resulting in the destruction of the spiroacetal structure to form other structures, which can be seen from FTIR (in the literature Figure 8 ) for explanation.

[0083] Compared with the prior art, the present invention has the following beneficial effects:

[0084] (1) The acetal structure is introduced into the end-capped benzoxazine resin of the present invention, which can make the resin degradable and facilitate recycling; (2) The acetal introduced into the end-capped benzoxazine resin of the present invention is a spirocyclic acetal, which has a certain rigidity, and gives the benzoxazine resin good heat resistance during the curing process and gives the cured resin heat resistance and rigidity; (3) The end-capped benzoxazine resin of the present invention can reduce the curing temperature of the diphthalonitrile compound containing the acetal structure; (4) The diphthalonitrile-based composite curing resin of the present invention can be degraded under acidic conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figures 1 to 12 The DSC curves of the blocked benzoxazines obtained in Example 1 and Examples 7 to 17 are shown in order.

[0086] Figure 13 to Figure 24 The NMR spectra of the blocked benzoxazines obtained in Example 1 and Examples 7 to 17 are shown in sequence. DETAILED DESCRIPTION

[0087] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art to the present invention based on the content of the present invention still belong to the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products.

[0088] The preparation of pentaerythritol bis(m-hydroxyphthalonitrile) acetal refers to patent CN112010833A or document "Ke Li, Hua Yin, Kun Yang, Pei Dai, Ling Han and Riwei Xu. Synthesis and properties of phthalonitrile-based resins containing spirocycle acetal. High Performance Polymers 2020".

[0089] The test methods used in the embodiments and comparative examples are as follows:

[0090] FTIR: IS-5 Fourier transform infrared spectrometer, KBr pellet method;

[0091] H-NMR: Bruker Avance 400 MHz, 25° C., deuterated chloroform; the present invention uses the integral area of ​​H in the group R and H in the terminal hydroxyl group in the NMR results to convert the possible n value.

[0092] DSC: TQ100, 10 °C / min, nitrogen atmosphere.

[0093] In the present invention, for the cured resin and the composite cured resin, the calculation method of the degradation degree (%) is as shown in the following formula:

[0094] Degradation degree % = [1-(W1-W2) / W1] × 100%

[0095] Wherein, W1 represents the initial weight of the cured resin, and W2 represents the weight of the degraded and insoluble residues.

[0096] Comparative Example 1

[0097] The raw materials were weighed according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2, and 3.44g (0.01mol) of pentaerythritol di-p-hydroxybenzaldehyde, 0.88g (0.01mol) of dibutylene glycol, 1.20g (0.04mol) of polyformaldehyde and 50mL of DMF were added to a 100ml three-necked flask, wherein the polyformaldehyde was added once; the reaction temperature was set to 115°C and the reaction was carried out for 24h. After the reaction was completed, the product was first washed with sodium bicarbonate aqueous solution (0.5M), filtered, and then washed with deionized water until neutral, filtered, and vacuum dried to constant weight (50°C) to obtain (p-SQ)-dibutylene glycol main chain benzoxazine, which was weighed and the yield was 54.3%. The pentaerythritol-p-hydroxybenzaldehyde-butylene diamine main chain benzoxazine resin was cured under the conditions of 120, 140, 160, 180, 200, 220, and 240° C., each temperature section was maintained for 2 hours, and finally cooled to room temperature. The obtained cured product was used as a comparative example for subsequent chemical degradation; the degradation experiment was carried out under the condition of ethanol: water: acetic acid (0.1 M) = 4:1:1.

[0098]

[0099] Comparative Example 2

[0100] Weigh the raw materials according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2.1, add 50mL DMF, 3.44g (0.01mol) pentaerythritol di-p-hydroxybenzaldehyde and 1.83ml (0.02mol) aniline in a 100ml three-necked flask, and stir and mix evenly; add 1.261g (0.042mol) polyformaldehyde to the three-necked flask in 2 to 4 times, place the three-necked flask in a low-temperature constant temperature reaction bath and stir for 30min, then gradually heat up to 95℃ and react at constant temperature for 10h. After the reaction is completed, wash the reaction product with a sodium hydroxide aqueous solution with a concentration of 1mol / L, filter it, wash it with deionized water until it is neutral, filter it, and vacuum dry it at 50℃ to constant weight.

[0101] Example 1

[0102] Weigh the raw materials according to the ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2 (molar ratio), and add 3.44g (0.01mol) of pentaerythritol di-p-hydroxybenzaldehyde, 0.44g (0.005mol) of diaminobenzaldehyde, 1.20g (0.04mol) of polyformaldehyde and 50mL of DMF in a 100ml three-necked flask, wherein the polyformaldehyde is added once; set the reaction temperature to 115℃, and react for 1h. Then add 0.93g (0.01mol) of aniline, and continue to react for 12h. After the reaction is completed, the product is first washed with sodium bicarbonate aqueous solution (5%), filtered, and then washed with deionized water until neutral, and then filtered. The product is vacuum dried to constant weight (70℃) to obtain (p-SQ)-diaminobenzidine aniline-terminated benzoxazine resin, which is weighed and has a yield of 59.1%. The molecular structure of the product is shown below.

[0103]

[0104] Example 2

[0105] The raw materials were weighed according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2. The synthesis process was the same as that in Example 1, except that the solvent was a mixed solvent of toluene and ethanol (toluene: ethanol = 2:1), the reaction temperature was 80°C, and the yield was 36.7%.

[0106] Example 3

[0107] The raw materials were weighed according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2. The synthesis process was the same as that in Example 1, except that a mixed solvent of DMF and dioxane (DMF: dioxane = 2:1) was used as the solvent. The yield was 49.8%.

[0108] Example 4

[0109] The raw materials were weighed according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2. The synthesis process was the same as that in Example 1, except that a mixed solvent of DMF and n-butanol (DMF: n-butanol = 2:1) was used as the solvent. The yield was 54.0%.

[0110] Example 5

[0111] The raw materials were weighed according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2. The synthesis process was the same as that in Example 1, except that a mixed solvent of DMF and butanediol (DMF: n-butanol = 2:1) was used as the solvent. The yield was 59.3%.

[0112] Example 6

[0113] The synthesis process was the same as in Example 1, except that aniline was added in one step. The reaction time was 12 h and the yield was 73.6%.

[0114] Example 7

[0115] The raw materials were weighed according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2. 3.44g (0.01mol) of pentaerythritol di-p-hydroxybenzaldehyde, 0.30g (0.005mol) of ethylenediamine, 1.20g (0.04mol) of polyformaldehyde and 50mL of DMF were added to a 100ml three-necked flask, and the polyformaldehyde was added once; the reaction temperature was set to 115°C and the reaction was allowed to proceed for 1h. 0.93g (0.01mol) of aniline was then added and the reaction continued for 12h. After the reaction was completed, the product was first washed with sodium bicarbonate aqueous solution (5%), filtered, and then washed with deionized water until neutral, and then filtered. The product was vacuum dried to constant weight (70°C) to obtain (p-SQ)-ethylenediamine aniline-terminated benzoxazine resin, which was weighed and had a yield of 63.3%. The molecular structure of the product is shown below.

[0116]

[0117] Example 8

[0118] Weigh the raw materials according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2, and add 3.44g (0.01mol) of pentaerythritol di-p-hydroxybenzaldehyde, 0.58g (0.005mol) hexamethylenediamine, 1.20g (0.04mol) polyformaldehyde and 50mL DMF in a 100ml three-necked flask, where polyformaldehyde is added once; set the reaction temperature to 115℃, and react for 1h. Then add 0.93g (0.01mol) aniline and continue to react for 12h. After the reaction is completed, the product is first washed with sodium bicarbonate aqueous solution (5%), filtered, and then washed with deionized water until neutral, and then filtered. The product is vacuum dried to constant weight (70℃) to obtain (p-SQ)-hexamethylenediamine aniline-terminated benzoxazine resin, weighed, and the yield is 53.5%. The molecular structure of the product is shown below.

[0119]

[0120] Example 9

[0121] The synthesis process was the same as in Example 8, except that 0.72 g (0.005 mol) of octanediamine was used instead of hexamethylenediamine to obtain (p-SQ)-octanediamine aniline-terminated benzoxazine resin with a yield of 52.3%. The molecular structure of the product is shown below.

[0122]

[0123] Example 10

[0124] The synthesis process was the same as in Example 9, except that 0.86 g (0.005 mol) of decanediamine was used instead of hexamethylenediamine to obtain (p-SQ)-decanediamine aniline-terminated benzoxazine resin with a yield of 50.7%. The molecular structure of the product is shown below.

[0125]

[0126] Embodiment 11

[0127] The synthesis process was the same as that of Example 9, except that 1.00 g (0.005 mol) of 1,12-diaminododecane was used instead of hexamethylenediamine to obtain (p-SQ)-1,12-diaminododecane aniline-terminated benzoxazine resin with a yield of 45.2%. The molecular structure of the product is shown below.

[0128]

[0129] Example 12

[0130] The synthesis process was the same as in Example 9, except that 0.98 g (0.005 mol) of 4,4'-diaminodiphenylmethane was used instead of hexamethylenediamine to obtain (p-SQ)-4,4'-diaminodiphenylmethane aniline-terminated benzoxazine resin with a yield of 31.1%. The molecular structure of the product is shown below.

[0131]

[0132] Embodiment 13

[0133] The synthesis process was the same as that of Example 9, except that 1.24 g (0.005 mol) of diaminodiphenyl sulfone was used instead of hexamethylenediamine to obtain (p-SQ)-diaminodiphenyl sulfone aniline-terminated benzoxazine resin with a yield of 30.0%. The molecular structure of the product is shown below.

[0134]

[0135] Embodiment 14

[0136] The synthesis process was the same as in Example 9, except that 1.19 g (0.005 mol) of 4,4'-methylenebis(2-methylcyclohexylamine) was used instead of hexamethylenediamine to obtain (p-SQ)-4,4'-methylenebis(2-methylcyclohexylamine)aniline-terminated benzoxazine resin with a yield of 63.6%. The molecular structure of the product is shown below.

[0137]

[0138] Embodiment 15

[0139] Weigh the raw materials according to the molar ratio of phenolic hydroxyl group: amine group: aldehyde group = 1:1:2, and add 1.72g (0.005mol) of pentaerythritol di-p-hydroxybenzaldehyde, 0.88g (0.01mol) of diaminobutane, 1.20g (0.04mol) of polyformaldehyde and 50mL of DMF in a 100ml three-necked flask, wherein the polyformaldehyde is added once; set the reaction temperature to 115℃, and react for 1h. Then add 0.94g (0.01mol) of phenol, and continue to react for 12h. After the reaction is completed, the product is first washed with sodium bicarbonate aqueous solution (5%), filtered, and then washed with deionized water until neutral, and then filtered. The product is vacuum dried to constant weight (70℃) to obtain (p-SQ)-diaminobutanephenol-terminated benzoxazine resin, which is weighed and has a yield of 50.5%. The molecular structure of the product is shown below.

[0140]

[0141] Example 16

[0142] The synthesis process was the same as that of Example 15, except that 1.98 g (0.01 mol) of 4,4'-diaminodiphenylmethane was used instead of butanediamine to obtain (p-SQ)-4,4'-diaminodiphenylmethane aniline-terminated benzoxazine resin with a yield of 33.3%.

[0143] The molecular structure of the product is shown below.

[0144]

[0145] Embodiment 17

[0146] The synthesis process was the same as that of Example 16, except that 2.38 g (0.01 mol) of 4,4'-methylenebis(2-methylcyclohexylamine) was used instead of diaminodiamine to obtain (p-SQ)-4,4'-methylenebis(2-methylcyclohexylamine)phenol-terminated benzoxazine resin with a yield of 59.7%. The molecular structure of the product is shown below.

[0147]

[0148] Embodiment 18

[0149] The degradation properties of benzoxazine resins containing acetal structures are illustrated below by taking the degradation products of pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine aniline terminated benzoxazine resin and pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine phenol terminated benzoxazine resin as examples.

[0150] Pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine aniline end-capped benzoxazine resin (synthesis conditions see Example 1) and pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine phenol end-capped benzoxazine resin (synthesis conditions see Example 16) are cured, each 20°C is a temperature gradient, each temperature gradient is reacted for 2h, and the temperature is raised from 120°C to 220°C to obtain a cured product. The cured product is placed in different solutions and heated to degrade, and after a certain period of degradation, filtered, the filter paper is dried to constant weight, and the degree of degradation is tested. The degradation conditions and results are listed in Table 1.

[0151] Table 1

[0152]

[0153]

[0154] It can be seen from Table 1 above that the cured resin after being cured with the blocked benzoxazine resin of the present invention has acidic degradability. Moreover, the higher the degradation temperature, the longer the degradation time, and the stronger the acidity of the acidic solution used for degradation, the more thorough the degradation; at the same time, the degradation degree of blocked benzoxazine is significantly higher than that of non-blocked benzoxazine.

[0155] Embodiment 19

[0156] The degradation of the cured product of pentaerythritol bis(p-hydroxybenzaldehyde)-butylene diamine aniline-terminated benzoxazine resin and pentaerythritol bis(m-hydroxyphthalonitrile) acetal is used as an example to illustrate the degradation performance of oxazine phthalonitrile resin containing acetal structure.

[0157] (1) Pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine aniline end-capped benzoxazine resin (synthesis conditions see Example 1) and pentaerythritol bis-p-hydroxyphthalonitrile resin are mixed in different mass ratios and then cured, with each 20°C being a temperature gradient, each temperature gradient reacting for 2h, and the temperature is raised from 120°C to 220°C to obtain a cured product. The cured product is placed in different solutions for heating and degradation, and after degradation for a certain period of time, filtered, the filter paper is dried to constant weight, and its degradation degree is tested. The degradation conditions and results are listed in Table 2. It can be seen that the introduction of pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine aniline end-capped benzoxazine has a promoting effect on the degradability of pentaerythritol type phthalonitrile resin. Among them, when the mass ratio of oxazine to phthalonitrile is 4:6, the cured product has good degradability.

[0158] Table 2

[0159]

[0160] (2) Pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine phenol end-capped benzoxazine resin (synthesis conditions see Example 16) and pentaerythritol bis-p-hydroxyphthalonitrile resin are mixed in different mass ratios and cured, with each 20°C being a temperature gradient, each temperature gradient reacting for 2h, and the temperature is raised from 120°C to 220°C to obtain a cured product. The cured product is placed in different solutions for heating and degradation, and after degradation for a certain period of time, filtered, the filter paper is dried to constant weight, and its degradation degree is tested. The degradation conditions and results are listed in Table 3. It can be seen that the introduction of pentaerythritol bis-p-hydroxybenzaldehyde-butylene diamine phenol end-capped benzoxazine has a promoting effect on the degradability of pentaerythritol type phthalonitrile resin. Among them, when the mass ratio of oxazine to phthalonitrile is 9:1, the cured product has good degradability. Although the degradation ability is reduced compared with the aniline end-capped benzoxazine resin, the degradation ability is slightly improved at room temperature.

[0161] Table 3

[0162]

[0163] Example 20 Thermal Stability

[0164] The resins obtained in Example 1 and Comparative Example 2 were subjected to TGA detection, and the structures were shown in Table 4 below.

[0165] Table 4:

[0166] Oxazine Type <![CDATA[T d5% (℃)]]> <![CDATA[T d10% (℃)]]> <![CDATA[Y c (780℃,%)]]> Example 1 255.69 287.77 46.15 Example 16 293.68 341.41 44.78 Comparative Example 2 230.30 304.20 48.36

[0167] It can be seen from Table 4 that compared with aniline-type oxazines, the blocked benzoxazines of the present invention have a higher initial decomposition temperature and better thermal stability. The reason may be that the rigidity of the spirocyclic structure gives benzoxazines a higher initial decomposition temperature, and the blocked benzoxazines of the present invention contain more spirocyclic structures, so their thermal stability is better.

[0168] Experimental Example Product Detection

[0169] (1) The (p-SQ)-diaminobenzene main chain benzoxazine obtained in Comparative Example 1 was tested:

[0170] The infrared detection results are as follows: 1501cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in diaminodiamine is 1233cm -1 The peak at 1119cm is the stretching vibration peak of the COC bond on the oxazine ring; -1 The CO characteristic peak of acetal is at 950cm-1, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm-1 The peak at 1164cm is the stretching vibration peak of COC on the acetal ring; -1 The oxazine ring is also the vibration peak of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks of asymmetric and symmetric stretching vibrations of -CH- on the methylene -CH2- in the acetal ring are at 3426cm -1 The stretching vibration peak of -OH can be observed, indicating that the two ends of oxazine are free hydroxyl groups of acetal bisphenol.

[0171] The results of NMR detection are as follows: At the chemical shift δ = 5.64ppm is the proton peak Ha, which belongs to the hydrogen on the middle carbon of the –O-CH2-N- structure of the oxazine ring. At δ = 4.85ppm is the proton peak Hb, which belongs to the hydrogen on the middle carbon of the Ar-CH2-N- structure of the oxazine ring. Because the oxazine ring is formed, the chemical shift and splitting of the hydrogen on the benzene ring have changed, and the proton peaks Hi and Hj both appear in the chemical shift range of δ = 6.9-7.1ppm. In addition, the chemical shifts of c, d, e, and f on the middle spiro structure have also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm, and some proton peaks overlap with Hb. The proton peak Hk belonging to diaminodiphenylamine appears in the range of 1.0ppm-2.7ppm. After peak area integration, S a :S b :S g :S c+d+e+f :S i :S j =2:2:1:8:1:1, and theoretically, the ratio of hydrogen at each position is consistent. Therefore, it can be determined that the (p-SQ)-butylene diamine main chain benzoxazine was successfully synthesized.

[0172] DSC detection shows that the first downward peak is the melting endothermic peak, with a melting peak top temperature of about 150°C and a very wide peak. The second upward peak is the curing exothermic peak of oxazine, with a peak top temperature of about 256°C.

[0173] (2) The (p-SQ)-butylene diamine aniline-terminated benzoxazine resin obtained in Example 1 was tested:

[0174] The infrared detection results are as follows: 1503cm -1 The single peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The -CH2- absorption vibration peak of diaminobutane is at 1234cm -1 The peak at 1119cm is the stretching vibration peak of the COC bond on the oxazine ring; -1The CO characteristic peak of acetal is at 951cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The peak at 1164cm is the stretching vibration peak of COC on the acetal ring; -1 The peaks at 2844 and 2937 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The asymmetric and symmetric stretching vibration absorption peaks of -CH- on the methylene -CH2- in the acetal ring can be observed at 750 and 690 cm-1. -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0175] The results of NMR detection are as follows: the newly appeared proton peak Hb at the chemical shift δ = 5.36ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N-structure; the newly appeared proton peak Hb' at the chemical shift δ = 4.63ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N-structure; and the proton peaks Ha and Ha' at δ = 5.46 and 4.67ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. Because the oxazine ring is generated, the chemical shift and splitting of the hydrogen on the benzene ring have changed, and the chemical shifts of c, d, e, and f on the middle spiro ring structure have also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the hydrogen on the -CH2- structure of diaminobenzene appears at 1.51 and 2.63 ppm, so it can be determined that the (p-SQ)-diaminobenzene aniline-terminated benzoxazine resin is successfully synthesized.

[0176] DSC detection shows that the melting peak of oxazine appears at 93°C. The solidification peak of oxazine begins to appear at 181°C, and the peak temperature is 210°C.

[0177] GPC detection showed that the number average molecular weight was 1390, and n=1.31.

[0178] (3) Testing of the (p-SQ)-ethylenediamineaniline-terminated benzoxazine resin obtained in Example 7

[0179] The infrared detection results are as follows: 1501cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in ethylenediamine is 1119cm -1 1234cm is the CO characteristic peak of acetal, that is, the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring.-1 The peak at 945cm is the stretching vibration peak of the COC bond on the oxazine ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The stretching vibration peak of COC on the acetal ring is 1168 cm -1 The peaks at 2849 and 2956 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The asymmetric and symmetric stretching vibration absorption peaks of -CH- on the methylene -CH2- in the acetal ring can be observed at 750 and 690 cm-1. -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0180] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.41ppm belongs to the hydrogen on the middle carbon of the –O-CH2-N-structure of the oxazine ring; the newly appeared proton peak Hb' at chemical shift δ = 4.54ppm belongs to the hydrogen on the middle carbon of the Ar-CH2-N-structure of the oxazine ring; and the proton peaks Ha and Ha' at δ = 5.46 and 4.68ppm are hydrogen on the middle carbon of the –O-CH2-N-structure and Ar-CH2-N-structure of the terminal oxazine ring, respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the -CH2-structure hydrogen on ethylenediamine appeared at 1.06 and 2.84ppm. Therefore, it can be determined that the (p-SQ)-ethylenediamine aniline-terminated benzoxazine resin was successfully synthesized.

[0181] DSC detection shows that there is a broad melting peak at 117°C. The first solidification peak of oxazine begins to appear at 150°C, with a peak temperature of 229°C. The second solidification peak of oxazine begins to appear at 229°C, with a peak temperature of 253°C.

[0182] GPC analysis was performed and n=1.2 was obtained based on the molecular weight.

[0183] (4) Testing of the (p-SQ)-hexamethylenediamineaniline-terminated benzoxazine resin obtained in Example 8

[0184] The infrared detection results are as follows: 1501cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in hexamethylenediamine is at 1233cm -1 The peak at 1115cm is the stretching vibration peak of the COC bond on the oxazine ring; -1The CO characteristic peak of acetal is at 945cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The peak at 1164cm is the stretching vibration peak of COC on the acetal ring; -1 The oxazine ring is also the vibration peak of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks of -CH- asymmetric and symmetric stretching vibrations on the methylene -CH2- in the acetal ring are at 750 and 690 cm -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0185] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.39ppm belongs to the hydrogen on the middle carbon of the –O-CH2-N-structure of the oxazine ring; the newly appeared proton peak Hb' at chemical shift δ = 4.51ppm belongs to the hydrogen on the middle carbon of the Ar-CH2-N-structure of the oxazine ring; and the proton peaks Ha and Ha' at δ = 5.49 and 4.68ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the -CH2-structure on hexamethylenediamine appeared at 1.23 and 2.68ppm. Therefore, it can be determined that the (p-SQ)-hexamethylenediamine aniline-terminated benzoxazine resin was successfully synthesized.

[0186] DSC detection shows that there is a melting peak at 107°C. The solidification peak of oxazine appears at 240°C, and the peak temperature is 255°C.

[0187] GPC analysis was performed and n=1.35 was obtained based on the molecular weight.

[0188] (5) Testing of the (p-SQ)-octanediamine aniline-terminated benzoxazine resin obtained in Example 9

[0189] The infrared detection results are as follows: 1503cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in octanediamine is at 1234cm -1 The peak at 1120 cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 930cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring;-1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The stretching vibration peak of COC on acetal is 1164 cm -1 The peaks at 2925 and 2849 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks of -CH- asymmetric and symmetric stretching vibrations on the methylene -CH2- in the acetal ring are at 750 and 690 cm -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0190] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.37ppm belongs to the hydrogen on the middle carbon of the –O-CH2-N-structure of the oxazine ring; the newly appeared proton peak Hb' at chemical shift δ = 4.51ppm belongs to the hydrogen on the middle carbon of the Ar-CH2-N-structure of the oxazine ring; and the proton peaks Ha and Ha' at δ = 5.46 and 4.68ppm are hydrogen on the middle carbon of the –O-CH2-N-structure and Ar-CH2-N-structure of the terminal oxazine ring, respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the -CH2-structure on octanediamine appears at 1.27 and 2.70ppm. Therefore, it can be determined that the (p-SQ)-octanediamine aniline-terminated benzoxazine resin was successfully synthesized.

[0191] DSC detection shows that there is a downward broad melting peak at 104°C. The solidification peak of oxazine appears at 244°C, and the peak temperature is 250°C.

[0192] GPC analysis was performed and the molecular weight was found to be n=1.18.

[0193] (6) Testing of the (p-SQ)-decanediamineaniline-terminated benzoxazine resin obtained in Example 10

[0194] The infrared detection results are as follows: 1500cm -1 The peak at 1380 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in decanediamine is at 1234cm -1 The peak at 1119cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 945cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1The stretching vibration peak of COC on acetal is 1168 cm -1 The peaks at 2931 and 2849 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks of -CH- asymmetric and symmetric stretching vibrations on the methylene -CH2- in the acetal ring are at 750 and 690 cm -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0195] The results of NMR detection are as follows: the newly appeared proton peak Hb at the chemical shift δ = 5.39ppm belongs to the hydrogen on the middle carbon of the –O-CH2-N-structure of the oxazine ring; the newly appeared proton peak Hb' at the chemical shift δ = 4.54ppm belongs to the hydrogen on the middle carbon of the Ar-CH2-N-structure of the oxazine ring; and the proton peaks Ha and Ha' at δ = 5.46 and 4.68ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the -CH2-structure on decanediamine appears in the range of 1.29 and 2.58ppm. Therefore, it can be determined that the (p-SQ)-decanediamine aniline-terminated benzoxazine resin was successfully synthesized.

[0196] DSC detection shows that there is a downward melting peak at 102°C from the DSC curve. The solidification peak of oxazine appears at 237°C, and the peak temperature is 243°C.

[0197] GPC analysis was performed and n=1.15 was obtained based on the molecular weight.

[0198] (7) Testing the (p-SQ)-1,12-diaminododecaneaniline-terminated benzoxazine resin obtained in Example 11

[0199] The infrared detection results are as follows: 1503cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in 1,12-diaminododecanediamine is 1234cm -1 The peak at 1114 cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 918cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The peak at 1168cm is the stretching vibration peak of COC on the acetal ring;-1 The peaks at 2925 and 2849 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks of -CH- asymmetric and symmetric stretching vibrations on the methylene -CH2- in the acetal ring are at 750 and 690 cm -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0200] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.37ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N-structure; the newly appeared proton peak Hb' at chemical shift δ = 4.54ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N-structure; and the proton peaks Ha and Ha' at δ = 5.46 and 4.68ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the -CH2- structure on 1,12-diaminododecane appears in the range of 1.24 and 2.74 ppm, so it can be determined that the (p-SQ)-1,12-diaminododecaneaniline-terminated benzoxazine resin was successfully synthesized.

[0201] DSC detection shows that there is a broad melting peak at 105°C. The solidification peak of oxazine appears at 240°C, and the peak temperature is 260°C.

[0202] GPC analysis was performed and n=1.08 was obtained based on the molecular weight.

[0203] (8) Testing the (p-SQ)-4,4'-diaminodiphenylmethane aniline-terminated benzoxazine resin obtained in Example 12

[0204] The infrared detection results are as follows: 1503cm -1 The peak at 1234cm is the stretching vibration peak of CC on the benzene ring; -1 The peak at 1114 cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 945cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The peak at 1160cm is the stretching vibration peak of COC on the acetal ring; -1 The peak at 826cm is the vibration peak of CNC on the oxazine ring. -1The peak at 2910 and 2837 cm is the peak of the para-substituted benzene ring, and the peak value is higher, which is significantly higher than that of the aliphatic main chain oxazine. Therefore, it is concluded that the oxazine main chain contains a 4,4'-diaminodiphenylmethane structure. -1 The absorption peaks are the asymmetric and symmetric stretching vibrations of -CH- on the methylene -CH2- in the acetal ring. -1 The peaks at 750 and 690 cm-1 are characteristic peaks of para-substituted and asymmetric 1,2,4-trisubstituted benzene rings. -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0205] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.39ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N-structure; the newly appeared proton peak Hb' at chemical shift δ = 4.51ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N-structure; and the proton peaks Ha and Ha' at δ = 5.46 and 4.61ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak Hg belonging to the methylene group on 4,4'-diaminodiphenylmethane appeared at 3.84ppm. Therefore, it can be determined that the (p-SQ)-4,4'-diaminodiphenylmethaneaniline-terminated benzoxazine resin was successfully synthesized.

[0206] DSC detection shows a downward melting peak at 90°C. The solidification peak of oxazine begins to appear at 256°C, with a peak temperature of 263°C.

[0207] GPC analysis was performed and the molecular weight was found to be n=1.11.

[0208] (9) Testing the (p-SQ)-diaminodiphenylsulfone aniline-terminated benzoxazine resin obtained in Example 13

[0209] The infrared detection results are as follows: 1503cm -1 The peak at 1234 cm is the stretching vibration peak of CC on the benzene ring. -1 The peak at 945cm is the stretching vibration peak of COC on the oxazine ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The stretching vibration peak of COC on acetal is 1164 cm -1 The peak at 1334 cm is the vibration peak of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1The vibration peaks of the sulfone group are at 2920 and 2849 cm -1 The absorption peaks at 826cm are the asymmetric and symmetric stretching vibrations of -CH- on the methylene -CH2- in the acetal ring. -1 The peaks at 750 and 691 cm-1 are characteristic peaks of para-substituted and asymmetric 1,2,4-trisubstituted benzene rings. -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0210] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.37ppm belongs to the hydrogen on the middle carbon of the –O-CH2-N-structure of the oxazine ring; the newly appeared proton peak Hb' at chemical shift δ = 4.51ppm belongs to the hydrogen on the middle carbon of the Ar-CH2-N-structure of the oxazine ring; and the proton peaks Ha and Ha' at δ = 5.46 and 4.68ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm, and the proton peaks Hg and Hh belonging to diaminodiphenyl sulfone appeared at 6.92ppm and 7.67ppm respectively. Therefore, it can be determined that the (p-SQ)-diaminodiphenyl sulfone aniline-terminated benzoxazine resin was successfully synthesized.

[0211] DSC detection shows that there is a downward melting peak at 107°C. The curing exothermic peak of oxazine appears at 261°C, and the peak temperature is 273°C.

[0212] GPC analysis was performed and n=1.05 was obtained based on the molecular weight.

[0213] (10) Testing the (p-SQ)-4,4'-methylenebis(2-methylcyclohexylamine)aniline-terminated benzoxazine resin obtained in Example 14

[0214] The infrared detection results are as follows: 1503cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The absorption vibration peak of -CH2- in 4,4'-methylenebis(2-methylcyclohexylamine) is 1459cm -1 The peak at 1234cm is the characteristic peak of methyl group in amine. -1 The peak at 1114 cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 945cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm-1 The stretching vibration peak of COC on acetal is 1164 cm -1 The peaks at 2925 and 2849 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks are the asymmetric and symmetric stretching vibrations of -CH- on the methylene -CH2- in the acetal ring. 826cm -1 The peaks at 750 and 691 cm-1 are characteristic peaks of para-substituted and asymmetric 1,2,4-trisubstituted benzene rings. -1 The characteristic peak of a monosubstituted benzene ring appears at , indicating that the aniline has been end-capped.

[0215] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.37ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N-structure; the newly appeared proton peak Hb' at chemical shift δ = 4.51ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N-structure; and the proton peaks Ha and Ha' at δ = 5.46 and 4.68ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peaks on the benzene ring are at 6.70-7.20ppm. The proton peaks Hg and Hj belonging to the methylene and methyl groups on 4,4'-methylenebis(2-methylcyclohexylamine) appear at 0.95ppm and 0.90ppm respectively, the proton peaks Hh, Hi and Hn belonging to the ring are at 1.20-1.70ppm, and the proton peak Hk on the ring appears at 2.99ppm. Therefore, it can be determined that (p-SQ)-4,4'-methylenebis(2-methylcyclohexylamine)aniline-terminated benzoxazine resin was successfully synthesized.

[0216] DSC detection shows that there is a downward melting peak at 102°C, and a solidification peak of oxazine appears at 194°C, with a peak temperature of 211°C.

[0217] GPC analysis was performed and n=1.08 was obtained based on the molecular weight.

[0218] (11) Testing the (p-SQ)-butylene diamine phenol-terminated benzoxazine resin obtained in Example 15

[0219] The infrared detection results are as follows: 1501cm -1 The single peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 The -CH2- absorption vibration peak of diaminobutane is at 1245cm -1The peak at 1120cm is the stretching vibration peak of the COC bond on the oxazine ring; -1 The CO characteristic peak of acetal is at 955cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The peak at 1164cm is the stretching vibration peak of COC on the acetal ring; -1 The vibration peaks of CNC on the oxazine ring are shown at 2844 and 2937 cm -1 The asymmetric and symmetric stretching vibration absorption peaks of -CH- on the methylene -CH2- in the acetal ring can be observed at 820cm -1 The peak at 750cm is the characteristic peak of asymmetric 1,2,4-trisubstituted benzene ring. -1 The characteristic peak of ortho-substitution of benzene ring appears, indicating that phenol has been capped.

[0220] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.36ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N-structure; the newly appeared proton peak Hb' at chemical shift δ = 4.51ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N-structure; and the proton peaks Ha and Ha' at δ = 5.37 and 4.54ppm are hydrogen on the middle carbon of the terminal oxazine ring –O-CH2-N-structure and Ar-CH2-N-structure respectively. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peaks on the benzene ring are at 6.70-7.20ppm. The proton peak Hg belonging to diaminodiamine appears at 1.20-1.70ppm. Therefore, it can be determined that the (p-SQ)-butylene diamine phenol-terminated benzoxazine resin was successfully synthesized.

[0221] DSC detection shows that there is a broad downward melting peak at 96°C. An upward oxazine solidification peak appears at 218°C, with a peak temperature of 234°C.

[0222] GPC analysis was performed and the molecular weight was found to be n=1.45.

[0223] (12) Testing the (p-SQ)-4,4'-diaminodiphenylmethane aniline-terminated benzoxazine resin obtained in Example 16

[0224] The infrared detection results are as follows: 1508cm -1 The peak at 1234cm is the stretching vibration peak of CC on the benzene ring; -1The peak at 1114 cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 945cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The peak at 1164cm is the stretching vibration peak of COC on the acetal ring; -1 The peak at 810cm is the vibration peak of CNC on the oxazine ring. -1 The peak at 2912 and 2844 cm-1 is the peak of the para-substituted benzene ring, and the peak value is higher, which is significantly higher than that of the aliphatic main chain oxazine. Therefore, it is concluded that the oxazine main chain contains a 4,4'-diaminodiphenylmethane structure. -1 The absorption peaks are the asymmetric and symmetric stretching vibrations of -CH- on the methylene -CH2- in the acetal ring. -1 The peak at 750cm is the characteristic peak of asymmetric 1,2,4-trisubstituted benzene ring. -1 The characteristic peak of ortho-substitution of benzene ring appears, indicating that phenol has been capped.

[0225] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.39ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N- structure. In addition, this peak coincides with the proton peak Ha of the terminal oxazine ring –O-CH2-N- structure; the newly appeared proton peak Hb' at chemical shift δ = 4.54ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N- structure; the proton peak Ha' at 4.59ppm is the hydrogen on the middle carbon of the terminal oxazine ring Ar-CH2-N- structure. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peaks on the benzene ring are at 6.70-7.20ppm. The proton peak Hg belonging to the methylene group on 4,4'-diaminodiphenylmethane appears at 3.83ppm. Therefore, it can be determined that the (p-SQ)-4,4'-diaminodiphenylmethanephenol-terminated benzoxazine resin was successfully synthesized.

[0226] DSC detection shows that there is no obvious melting peak from the DSC curve. An upward oxazine solidification peak appears at 262°C, and the peak temperature is 269°C.

[0227] GPC analysis was performed and n=1.14 was obtained based on the molecular weight.

[0228] (13) Testing the (p-SQ)-4,4'-methylenebis(2-methylcyclohexylamine)phenol-terminated benzoxazine resin obtained in Example 17

[0229] The infrared detection results are as follows: 1503cm -1 The peak at 1383 cm is the stretching vibration peak of CC on the benzene ring. -1 1460cm is the absorption vibration peak of -CH2- in 4,4'-methylenebis(2-methylcyclohexylamine). -1 The peak at 1240cm is the characteristic peak of the methyl group in the amine. -1 The peak at 1119cm is the stretching vibration peak of COC on the oxazine ring; -1 The CO characteristic peak of acetal is at 955cm, which is the CO characteristic absorption peak of the tertiary carbon connected to two O atoms in the acetal ring; -1 The absorption vibration peak of the oxazine ring is at 1078cm -1 The stretching vibration peak of COC on acetal is 1164 cm -1 The peaks at 2912 and 2849 cm are the vibration peaks of CNC on the oxazine ring. It can be seen that the oxazine ring exists. -1 The absorption peaks of asymmetric and symmetric stretching vibrations of -CH- on the methylene -CH2- in the acetal ring are at 826cm -1 The peak at 750cm is the characteristic peak of asymmetric 1,2,4-trisubstituted benzene ring. -1 The characteristic peak of ortho-substituted benzene ring appears at the 40°C, indicating that phenol has been end-capped.

[0230] The results of NMR detection are as follows: the newly appeared proton peak Hb at chemical shift δ = 5.37ppm belongs to the hydrogen on the middle carbon of the oxazine ring –O-CH2-N- structure. In addition, this peak coincides with the proton peak Ha of the terminal oxazine ring –O-CH2-N- structure; the newly appeared proton peak Hb' at chemical shift δ = 4.52ppm belongs to the hydrogen on the middle carbon of the oxazine ring Ar-CH2-N- structure; the proton peak Ha' at 4.54ppm is the hydrogen on the middle carbon of the terminal oxazine ring Ar-CH2-N- structure. In addition, the chemical shifts of c, d, e, and f on the middle spiro ring structure also changed from the original 4.5ppm-3.6ppm to 4.9ppm-3.6ppm. The proton peak on the benzene ring is at 6.70-7.20ppm. The proton peaks Hg and Hj belonging to the methylene and methyl groups on 4,4'-methylenebis(2-methylcyclohexylamine) appear at 0.94ppm and 0.90ppm respectively, the proton peaks Hh, Hi and Hn belonging to the ring are at 1.20-1.70ppm, and the proton peak Hk on the ring appears at 2.99ppm. Therefore, it can be determined that (p-SQ)-4,4'-methylenebis(2-methylcyclohexylamine)phenol-terminated benzoxazine resin was successfully synthesized.

[0231] DSC detection shows that there is a broad downward melting peak at 105°C. The solidification peak of oxazine appears at 234°C, and the peak temperature is 244°C.

[0232] GPC analysis was performed and n=1.09 was obtained based on the molecular weight.

[0233] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A bisphthalonitrile-based composite material, comprising a blocked benzoxazine resin and a bisphthalonitrile compound containing a spirocyclic acetal structure, wherein the bisphthalonitrile compound containing a spirocyclic acetal structure is a pentaerythritol-type phthalonitrile resin, and the blocked benzoxazine resin is a main chain polymer, wherein the main chain polymer has at least one of the repeating units represented by formula (I-1) to formula (I-3) in its molecular chain: Formula (I-1) Formula (I-2) Formula (I-3) The molecular chain end of the main chain polymer is a structure shown in one of formulas (I-4) to (I-9): Formula (I-4) Formula (I-5) Formula (I-6) Formula (I-7) Formula (I-8) Formula (I-9) In formula (I-1) to (I-3) and (I-7) to (I-9), each R is independently selected from at least one of a C2 to C20 alkyl group and a C6 to C20 alicyclic group; in formula (I-4) to (I-6), R′ is selected from one of an aliphatic group, an alicyclic group, and an aromatic group; in formula (I-7) to (I-9), R1″ to R4″ are independently selected from one of hydrogen, an aliphatic group, an alicyclic group, and an aromatic group.

2. The bis(o-phthalonitrile)-based composite material according to claim 1, wherein In formula (I-4) to formula (I-6), R′ is selected from C1-C12 alkyl, C6-C12 alicyclic group, phenyl; and / or, In formula (I-7) to formula (I-9), R1″ to R4″ are each independently selected from hydrogen, a C1-C12 alkyl group, a C6-C12 alicyclic group or a phenyl group.

3. The bis(o-phthalonitrile)-based composite material according to claim 1, wherein In formula (I-1) to (I-3) and formula (I-7) to (I-9), each R is independently selected from at least one of a C2 to C10 alkyl group and a cyclohexyl group; and / or, In formula (I-4) to formula (I-6), R′ is selected from a C1-C6 alkyl group, a C6-C8 alicyclic group or a phenyl group; and / or, In formula (I-7) to formula (I-9), R1″ to R4″ are each independently selected from hydrogen, a C1 to C6 alkyl group, a C6 to C8 alicyclic group or a phenyl group.

4. The bis(o-phthalonitrile)-based composite material according to any one of claims 1 to 3, characterized in that: The preparation method of the blocked benzoxazine resin comprises: mixing a monoamine compound and / or a monophenol compound with a bisphenol compound containing a spiroacetal structure, a diamine compound, and an aldehyde compound to react, and performing post-treatment to obtain the blocked benzoxazine resin.

5. The bis(o-phthalonitrile)-based composite material according to claim 4, characterized in that: The diamine compound is selected from at least one of aliphatic diamines and alicyclic diamines; and / or, The aldehyde compound is selected from paraformaldehyde and / or formaldehyde solution; and / or, The monophenol compound is selected from at least one of phenol and substituted phenol.

6. The bis(o-phthalonitrile)-based composite material according to claim 5, characterized in that: The aldehyde compound is selected from paraformaldehyde; and / or, The monoamine compound is at least one selected from aniline, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine and neopentylamine.

7. The bis(o-phthalonitrile)-based composite material according to claim 4, characterized in that: The molar ratio of the bisphenol compound containing the spiroacetal structure, the diamine compound and the aldehyde compound is 1:1:(2-5); and / or, The molar ratio of the total mole of the monoamine compound and the monophenol compound to the molar ratio of the bisphenol compound containing the spiroacetal structure is (1-2):1; and / or, The molar ratio of the monoamine compound to the monophenol compound is (0-10):(10-0).

8. The bis(o-phthalonitrile)-based composite material according to claim 7, characterized in that: The molar ratio of the bisphenol compound containing the spiroacetal structure, the diamine compound and the aldehyde compound is 1:1:(2-3); and / or, The molar ratio of the total mole of the monoamine compound and the monophenol compound to the mole of the bisphenol compound containing the spiroacetal structure is (1-1.2):

1.

9. The bis(o-phthalonitrile)-based composite material according to claim 4, characterized in that: The method comprises the following steps: Step 1, mixing the aldehyde compound, the bisphenol compound containing a spirocyclic acetal structure, the diamine compound and a solvent, and heating them for a preliminary reaction; Step 2: After the reaction is completed, add a monoamine compound and / or a monophenol compound for end-capping; Step 3: After the end-capping is completed, post-treatment is performed to obtain the end-capped benzoxazine resin.

10. The bis(o-phthalonitrile)-based composite material according to claim 9, characterized in that: In step 1, the solvent is selected from one or more of ethanol, methanol, isopropanol, butanol, isobutanol, tetrahydrofuran, dioxane, toluene, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; and / or, In step 1, the temperature of the pre-reaction is 80-150° C.; and / or, In step 1, the pre-reaction time is 0.2 to 5 hours; and / or, In step 2, the end-capping is performed for 5 to 20 hours; and / or, In step 3, the post-treatment includes alkali washing, water washing, and solvent removal treatment.

11. The bis(o-phthalonitrile)-based composite material according to claim 10, characterized in that: In step 1, the temperature of the pre-reaction is 90-130° C.; and / or, In step 1, the pre-reaction time is 0.5 to 2 hours; and / or, In step 2, the end-capping is performed for 10 to 12 hours.

12. The bis(o-phthalonitrile)-based composite material according to claim 1, characterized in that: Based on the total weight of the diphthalonitrile-based composite material of 100wt%, the blocked benzoxazine resin accounts for 10-90wt%; the diphthalonitrile compound containing a spirocyclic acetal structure accounts for 10-90wt%.

13. The bis(o-phthalonitrile)-based composite material according to claim 12, characterized in that: Based on the total weight of the diphthalonitrile-based composite material of 100wt%, the blocked benzoxazine resin accounts for 10-50wt%; the diphthalonitrile compound containing a spirocyclic acetal structure accounts for 50-90wt%.

14. A diphthalonitrile-based composite cured resin, which is a ring-opening cured product of the diphthalonitrile-based composite material according to any one of claims 1 to 13.

15. The bisphthalonitrile-based composite curing resin according to claim 14, characterized in that: The ring-opening curing is carried out at 120-220°C.

16. The bis-phthalonitrile-based composite curing resin according to claim 14, characterized in that: The temperature was raised from 120°C to 220°C, with each temperature gradient being 10 to 30°C, and each temperature gradient was reacted for 1 to 3 hours.

Citation Information

Patent Citations

  • Bisphthalonitrile compound containing acetal structure, polymer and preparation method and application thereof

    CN112010833A

  • Main-chain benzoxazine oligomer compositions, and method for the preparation thereof

    CN103097422A

  • Benzoxazine resin with spirocyclic acetal structure and preparation method thereof

    CN110551140A

  • Bio-based degradable benzoxazine resin, and preparation method, cured resin, compound and degradation method thereof

    CN112442158A